Fruit and vegetable diseases - Mukerji, K. G. (Disease management of fruits and vegetables, 2004)
During the past twentieth century, plant pathology has witnessed a dramatic advancement in management of plant diseases through in-depth investigations of host parasite interactions, integration of new concepts, principles and approaches. Our effort in brining out this book is to compile the achievements of modern times with regards to disease management of fruits which otherwise is widely dispersed in various scientific journals, books and government reports and to develop future strategies for the millennium. The chapters on individual crops are contributed by leading plant pathologists having authority in the respective field at international level. Each chapter includes the diseases of economic importance describing their history, distribution, symptoms, epidemiology, and integrated management approaches being adopted worldwide. Each chapter is vividly illustrated to make it more understandable to students, research and extension workers, planners, administrators and other end users citing pertinent references.